The Influence of Capital, Financial Literacy, and Technology in the Development of MSMEs (Case Study on Fintech Peer To Peer Lending Customers in Klaten Regency) (Universitas Negeri Semarang, 2022)
The aims of this study were (1) to determine the capital factor for the development of small and medium enterprises for Fintech Peer to-Peer Landing customers in Klaten Regency; (2) to determine the financial literacy factor for the development of small and medium enterprises for Fintech Peer to Peer Landing customers in Klaten Regency; and (3) to find out the technological factors on the development of small and medium enterprises for Fintech Peer to Peer Landing customers in Klaten Regency. The method used is the multiple linear regression analysis methods. The population in this study are Fintech Peer-to-Peer Landing customers in Klaten Regency. A sample of 100 respondents was taken using the Slovin method. The results of this study indicate that there is a simultaneous influence on the variables of capital, financial literacy, and technology on the development of MSME Fintech Peer to-Peer Landing customers, Klaten Regency. This can be seen from the significant value of less than 0.05 (0.000 0.05) and the F test result of 539.760. The results of this study also show that the t-count value for the capital variable is 4.758, financial literacy is 3.627 and technology is 4.673 which is greater than the t-table of 1.660. It can be stated that the independent variables have a significant influence on the development of MSMEs on Fintech Peer-to-Peer Landing customers in Klaten Regency.